1997
DOI: 10.3141/1598-04
|View full text |Cite
|
Sign up to set email alerts
|

Transit and Carpool Commuting and Household Vehicle Trip Making: Panel Data Analysis

Abstract: Most of the evaluation of commute trip reduction programs centers on the effect on reducing driveway trips at the work site. Little has been done to explore the effects of such programs on overall trip making. This work is meant to help understand this relationship by determining the association between transit and carpool commuting and overall household vehicle trip making. Household activity models have indicated that an individual's travel decisions influence (and are influenced by) the decisions of other h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Most research has focused on how carpooling mode share changes with time, fuel costs, socio-economic characteristics like income, economic growth, availability of jobs, etc. (Bard, 1997;Doherty et al, 2002;Ferguson, 1997). A great deal of the research done on carpool mode share has used the National Household Travel Survey (NHTS) dataset which is limited to socio-economic and demographic variables.…”
Section: ___________mentioning
confidence: 99%
“…Most research has focused on how carpooling mode share changes with time, fuel costs, socio-economic characteristics like income, economic growth, availability of jobs, etc. (Bard, 1997;Doherty et al, 2002;Ferguson, 1997). A great deal of the research done on carpool mode share has used the National Household Travel Survey (NHTS) dataset which is limited to socio-economic and demographic variables.…”
Section: ___________mentioning
confidence: 99%
“…Brownstone and Golob (1992) address Teal’s concern by building a model that predicts which kinds of incentives favor ride sharing: HOV lanes, guaranteed rides home, preferential parking, subsidies, or an amorphous category of other incentives. Bard (1997) looks at how carpooling decreases the total number of trips taken by a household, but does not extend this to traffic outcomes or welfare calculations. Plotz, Konduri, and Pendyala (2010) put bounds on how many carpools were formed because of HOV lanes.…”
Section: Additional Models Of Hov and Hot Lanesmentioning
confidence: 99%
“…It is believed that, with provision of HOV lanes in congested corridors, some solo drivers will form rideshare partnerships with family, friends, or coworkers to save travel time. Household activity studies have suggested that one household member's travel decision will influence the decisions of others in the same household and vice versa (2). Thus, if one person chooses to carpool, the likelihood that another household member will do so increases.…”
mentioning
confidence: 99%